1994
DOI: 10.1080/00103629409369062
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts of nitrapyrin, dicyandiamide, and iso‐butylidene diurea effects on total inorganic soil nitrogen

Abstract: While much research has been done with nitrification inhibitors, little information exists on their effects on total inorganic soil nitrogen (N) (TISN) (NH 4 + -N + NO 3 --N). The objective of this study was to compare the effects of 2-chloro-6-(trichloromethyl)-pyridine (nitrapyrin) and dicyandiamide (DCD) on TISN concentrations and to compare the effects of the nitrification inhibitors with those of IBDU, a slow release N source. Effects of the three N-amendments were compared in soil planted to potato (Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…This could be because spring conditions generally were wet (Table 3), gaseous N losses in claypan soils as high as 30% have been reported (Wilkison et al, 2000), and summer conditions were favorable for high yields. Similar effects between nitrapyrin and pronitridine were expected as Martin et al, (1994) reported finding similar effects of nitrapyrin and DCD on total inorganic soil N. Note. † Calculated as: kg grain produced kg N -1 applied (Fixen et al, 2014).…”
Section: Precipitationsupporting
confidence: 62%
See 1 more Smart Citation
“…This could be because spring conditions generally were wet (Table 3), gaseous N losses in claypan soils as high as 30% have been reported (Wilkison et al, 2000), and summer conditions were favorable for high yields. Similar effects between nitrapyrin and pronitridine were expected as Martin et al, (1994) reported finding similar effects of nitrapyrin and DCD on total inorganic soil N. Note. † Calculated as: kg grain produced kg N -1 applied (Fixen et al, 2014).…”
Section: Precipitationsupporting
confidence: 62%
“…Loss of N to the atmosphere may approach 30% (Wilkison et al, 2000). Numerous studies have investigated nitrification inhibitors in soils at high risk of leaching potential, and once N is leached out of the root zone plant N uptake is reduced (Mason, 1987;McCarty & Bremner, 1989;Francis et al, 1993;Martin et al, 1994). A new nitrification inhibitor, pronitridine (CAS RN 1373256-33-7, Centuro™, Koch Agronomic Services, Witchita, KS), was recently developed to enhance the efficiency of N applications in corn (Vetsch & Schwab, 2014;Gabrielson & Epling, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hendrickson et al (1978) showed at least partial inhibition with nitrapyrin for 49 days on this soil. Martin et al (1994) found few differences between DCD and nitrapyrin effectiveness on maintaining soil inorganic N fractions on sandy soils in Florida as did several Illinois researchers (Schmitt 1983;Sawyer 1985).…”
Section: Resultsmentioning
confidence: 84%
“…Corn research on coarse-textured soils has shown that while yield and/or apparent N recovery could be improved with inhibitor use in combination with preplant N, relatively few benefits have been seen when inhibitors were used with sidedress or split N applications (Chancy and Kamprath 1982;Zublena 1984;Reeves and Touchton 1986;Frye et al 1989;Malzer et al 1989). These and other studies have shown that inhibitors can effectively block nitrification for 35 to 50 days on sands depending on soil temperature (Hendrickson et al 1978;Schmitt 1983;Martin et al 1994). However, the benefit to the crop is dependent upon the existence of environmental conditions conducive to N losses prior to when the N is taken up by the crop.…”
mentioning
confidence: 95%